The Society of Thoracic Surgeons Congenital Heart Surgery Database: 2019 Update on Research - Jacobs, Marshall L. (Ann Thorac Surg, 2019)
As the largest congenital and pediatric cardiac surgical clinical data registry in the world, the Society of Thoracic Surgeons Congenital Heart Surgery Database (STS CHSD) serves as a platform for reporting of outcomes and for quality improvement. In addition, it is an important source of data for clinical research and for innovations related to quality measurement. Each year, several teams of investigators undertake analyses of data in the STS CHSD pertaining to the surgical management of specific diagnostic and procedural groups, as well as specific processes of care and their associations with patient characteristics across centers participating in the STS CHSD, and with outcomes. Additional ongoing projects involve the development of new or refined metrics for quality measurement and reporting of outcomes and center level performance. The STS, through its Workforce for National Databases and the STS Research Center and Workforce on Research Development provides multiple pathways through which investigators may propose and carry out outcomes research projects based on STS CHSD data. This article reviews research published within the past year.